The Romanic Review: tomo 43 (1952), tomo 44 (1953), tomo 45 (1954). - M. A. Vergara (Nueva Revista de Filología Hispánica, 1971)
Se reseñó: The Romanic Review: tomo 43 (1952), tomo 44 (1953), tomo 45 (1954).